APPLICATION THE INVESTIGATION GROUP METHOD TO IMPROVE STUDENTS COMPETENCE STANDARD IN ARTS APPRECIATION ON THE SUBJECT OF VISUAL ARTS FOR STUDENTS OF PGSD UNNES - Nurharini, Atip (Jurnal Penelitian Pendidikan, 2013)
Lecturers have a responsibilityto make their learning process positive and productive. Just likeother learnings, visual art learning also needs innovative learning methods. But this statement is not in line with the reality. In general the visual art learning still describes authoritative educational practices and lecturer-centered-learning.The lack ofinteractive communication between faculty and students and learning resources, students tend to appreciate, passive and accept just lectures given by lecturer. At the time of learning student appreciation rate still low. It is seen when students are faced with works that have meaning and value of tall. Student difficulties in understanding, appreciate andevaluate to performent art. Oflearning activities the impact of low competencestudentsin the art appreciates. To improvethe learning activities researchers applied the method of group investigation. Problems in the reseach such as what the application of group method of investigation can increase motivation, responbilitas, and the standards of competence students. The purpose of research are to describe the application of group method of investigation can increase motivation, responbilitas, and the standards of competence students. The research designusing theprocedurePTK that implemented in two cycle, each cycle consist of planing, acting, and reflection. Research subject are lectures and strudents even semester 2012 consisting of 8 girls and 7 boys. Data collection techniques are observation, interview, document and field record. Data analysis using descriptive quantitative and qualitative. The results of the study shows that there is improvement on studentsâ motivation, motivation, responbilitas, andthe standards of competence students. Improve Students Competence occurs ineachindicator, responbilitas 5 indicator, and competence students on appreciatethework of art 5 indicator. Conclusionsof the researchis that The Investigation Group Method can Improvestudents motivation, responbilitas, andthe standards of competencein appreciating fowadrsâ visual art creation. Sugestions of the research are that (1). Lecturers should apply this method to improve studentsâ motivation, (2). Students shouldndo visual arts appreciation to improve cognitive, affective, and psichomotoric competence, (3). Education institution should support any learning method innovation invention to develop the quality of the institution.